The Cost-Effectiveness of Alogliptin Versus Sulfonylurea as Add-on Therapy to Metformin in Patients with Uncontrolled Type 2 Diabetes Mellitus. Issue 4 (December 2016) - Gordon, Jason; McEwan, Phil; Hurst, Michael; Puelles, Jorge
Abstract Introduction ENDURE (ClinicalTrials.gov identifier, NCT00856284), a multicenter, double-blind, active-controlled study of 2639 patients with uncontrolled type 2 diabetes mellitus (T2DM), found that metformin in combination with alogliptin (12.5 and 25 mg doses), when compared to standard add-on therapy (sulfonylurea, SU), exerted sustained antihyperglycemic effects over 2 years. This economic analysis of ENDURE aimed to quantify the relationship between increased glycemic durability and cost-effectiveness of alogliptin in the UK clinical setting, and communicate its sustained glycemic benefit in economic terms. Methods Using baseline characteristics and treatment effects from the ENDURE trial population, between-group cost-effectiveness analyses compared the combined use of metformin and alogliptin (MET + ALO12.5/25 ) in patients with inadequately controlled T2DM, as an alternative to metformin and SU (MET + SU). In scenario analyses, an intragroup cost-effectiveness analysis compared MET + ALO12.5/25 with MET + SU; a between-group cost-effectiveness analysis also compared MET + ALO12.5/25 versus MET + SU within a subpopulation of patients who achieved HbA1c control (<7.5%) at 2 years on study drug. Results Compared with baseline profiles of patients, combination therapies with alogliptin or SU were associated with improvements in length and quality of life and were cost-effective at established norms. Despite increased drug acquisition costs, alogliptin at 12.5 mg and 25 mg doses resulted in greater predicted lifetime quality-adjusted life year (QALY) gains with associated incremental cost-effectiveness ratios (ICERs) of £10, 959/QALY and £7217/QALY compared to SU, respectively. Conclusion The ENDURE trial and the present cost-effectiveness analysis found that the glycemic durability of alogliptin therapy was associated with improved long-term patient outcomes, QALY gains, and ICERs that were cost-effective when evaluated against standard threshold values. Alogliptin therefore represents a cost-effective treatment alternative to SU as add-on therapy to metformin in patients with poorly managed T2DM. Funding Takeda Development Centre Europe Ltd.